Turnaround times - the Achilles' heel of community screening and testing in Cape Town, South Africa: A short report - James D. Porter; Robert Mash; Wolfgang Preiser (AOSIS, 2020)
Early in the course of the coronavirus infection disease 2019 (COVID-19) pandemic in South Africa, the Department of Health implemented a policy of community screening and testing (CST). This was based on a community-orientated primary care approach and was a key strategy in limiting the spread of the pandemic, but it struggled with long turnaround times (TATs) for the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) reverse transcriptase polymerase chain reaction test. The local experience at Symphony Way Community Day Centre (Delft, Cape Town), highlighted these challenges. The first positive tests had a median TAT of 4.5 days, peaking at 29 days in mid-May 2020. Issues that contributed to long TATs were unavailability of viral transport medium, sample delivery and storage difficulties, staffing problems, scarcity of testing supplies and other samples prioritised over CST samples. At Symphony Way, many patients who tested COVID-19 positive had abandoned their self-isolation because of the delay in results. Employers were unhappy with prolonged sick leave whilst waiting for results and patients were concerned about not getting paid or job loss. The CST policy relies on a rapid TAT to be successful. Once the TAT is delayed, the process of contacting patients, and tracing and quarantining contacts becomes ineffective. With hindsight, other countries' difficulties in upscaling testing should have served as warning. Community screening and testing was scaled back from 18 May 2020, and testing policy was changed to only include high-risk patients from 29 May 2020. The delayed TATs meant that the CST policy had no beneficial impact at local level.